Peranan Psychological Capital Karyawan Dalam Mendorong Ekspektasi Kinerja Perusahaan - Sari, Yunita; Yunianto, Andika (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
The world's economic growth has made competition in the business world even tighter,so companies must have good achievements to get success in the business world. This isthe biggest challenge for organizations to survive and adapt to any changes that occur.For that the company must be able to increase the ability and potential of employees.Efforts to improve the quality and effectiveness of employees need serious attention bythe company by referring to the development of information technology and thereadiness of human resources. The work effectiveness of company employees is not onlydetermined by the rules and Standard Operational Procedure (SOP). Employees with ahigh level of performance expectations show a positive attitude towards their work, onthe other hand someone who does not have performance expectations with their workshows a negative attitude towards work. Therefore, the company is expected to generatepsychological capital that can boost employee performance expectations, wherepsychological capital reflects a positive psychological condition. By measuring thesuccess of the application of the psychological capital role of employees in encouragingexpectations of company performance, it is able to generate employee confidence insolving problems and success at work